Comparative study regarding the level of anxiety in various categories of athletes - Ababei, C. (Annals of "Dunarea de Jos" University of Galati: Physical Education and Sport Management, 2020)
The Romanian Language Dictionary (2009) defines anxiety as inquietude, unrest, fear. The athletes' emotional states can change easily, especially in less experienced athletes, often near a competition that demands reaching a goal, or when they find themselves in new situations. This can cause them to block or have no reaction in key moments. Professional sports regard anxiety as a normal reaction of the athlete's body, believing that in this manner it adapts to new conditions and functional parameters. The study was based on the hypothesis stating that anxiety could have various levels in athletes before a competition, according to their sport. The research was conducted on 45 athletes practicing wrestling, track and field, and boxing at a national level, for various Bacau sports clubs. The main research method for this study was the inquiry, and the working instrument was the questionnaire - J. Taylor's anxiety scale.